2015
DOI: 10.1093/epirev/mxu009
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Hazards Exposure and Respiratory Health of Iraq and Afghanistan Veterans

Abstract: More than 2.6 million military personnel have been deployed to recent conflicts in Iraq and Afghanistan and were likely exposed to a variety of airborne hazards during deployment. Despite several epidemiologic reports of increased respiratory symptoms, whether or not these respiratory illnesses lead to reductions in lung function and/or specific pulmonary disease is unclear. We reviewed data published from 2001 to 2014 pertaining to respiratory health in military personnel deployed to Iraq and Afghanistan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 107 publications
0
43
1
1
Order By: Relevance
“…After the Persian Gulf war, there was a prominent focus on CMI (called Gulf War Illness), the associated poor functioning [7], and the possible overlap of this condition with PTSD symptoms [16]. In contrast, the clinical focus for OIF/OEF Veterans has been on multiple diagnoses, each of which can be associated with significant physical symptoms, including chronic pain, PTSD, mTBI, depression, and polysubstance abuse [16,[35][36][37]. Our study was limited in that we only assessed PTSD and pain symptoms and did not have measures of these other common postdeployment health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…After the Persian Gulf war, there was a prominent focus on CMI (called Gulf War Illness), the associated poor functioning [7], and the possible overlap of this condition with PTSD symptoms [16]. In contrast, the clinical focus for OIF/OEF Veterans has been on multiple diagnoses, each of which can be associated with significant physical symptoms, including chronic pain, PTSD, mTBI, depression, and polysubstance abuse [16,[35][36][37]. Our study was limited in that we only assessed PTSD and pain symptoms and did not have measures of these other common postdeployment health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Hazardous environmental exposures reported by veterans from operations in Iraq and Afghanistan include dust storms, smoke from burning trash, oil fires, vehicle exhaust, chemicals, and petrochemical fuel exposures [8]. A retrospective analysis showed that almost all (94 percent) of veterans of these two conflicts reported hazardous exposures during their deployment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, while documented evidence of hazardous exposures is widely available in the literature [3,5,6,8,9,10,11,12], data on ‘near miss’ incidents have been more difficult to obtain, as most of the literature focusses on dangerous and hazardous exposures that cause immediate or latent health problems [3]. Reporting near misses may serve to reduce instances of exposures and incidents, highlighting the importance of creating a workplace environment which encourages near miss reporting as collaborative as opposed to punitive [17].…”
Section: Introductionmentioning
confidence: 99%
“…E xposure to a variety of airborne hazards during deployment to Iraq or Afghanistan, such as elevated levels of particulate matter, 1,2 has been implicated in the increased reporting of respiratory symptoms and diseases in military personnel since 2001. [3][4][5] Although military personnel may be uniquely vulnerable and susceptible to airborne hazards, 6 a causal relationship between deploymentrelated exposures and respiratory disease has not been established in recent combat veterans. Despite several reviews, 3,6-8 recommendations, 3,9,10 and the launch of a national registry database, 11 few studies are available that document objective pulmonary function among veterans who had deployed to Southwest Asia.…”
mentioning
confidence: 99%
“…[12][13][14] At present, the literature is composed predominantly of retrospective studies and surveys, which have recently been reviewed elsewhere. 6 Morris et al 13 recently performed a prospective evaluation of 50 active duty military personnel who presented with new-onset respiratory symptoms within 6 months of returning from deployment to Iraq or Afghanistan. Airway hyperreactivity was the most consistent abnormality in this sample with 36% receiving this diagnosis, supporting other reports of new-onset respiratory symptoms and asthma in returning military personnel.…”
mentioning
confidence: 99%